2013
DOI: 10.1016/j.fuel.2012.06.094
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous oil recovery and residual gas storage: A pore-level analysis using in situ X-ray micro-tomography

Abstract: We imaged sandstone cores at residual gas saturation (S gr) with synchrotron radiation at a nominal resolution of (9 µm) 3. We studied two three-phase flooding sequences: 1. gas injection into a core containing oil and initial water followed by a waterflood (gw process); 2. gas injection into a waterflooded core followed by another waterflood (wgw process). In the gw flood we measured a significantly higher S gr (= 20.6%; S gr in the wgw flood was 5.3%) and a significantly lower residual oil saturation (S or ;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
90
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 59 publications
9
90
0
1
Order By: Relevance
“…In a in the safety and permanence of the storage and contributes the majority of estimated storage 46 capacity in regional assessments [6][7][8][9] . A large body of recent work has reported observations of 47 trapping in the laboratory [10][11][12] and modeling to analyze the implications for CO 2 migration 13 …”
mentioning
confidence: 99%
“…In a in the safety and permanence of the storage and contributes the majority of estimated storage 46 capacity in regional assessments [6][7][8][9] . A large body of recent work has reported observations of 47 trapping in the laboratory [10][11][12] and modeling to analyze the implications for CO 2 migration 13 …”
mentioning
confidence: 99%
“…This considerable potential is of great interest for Enhanced Oil Recovery (EOR) methods which fall into three main categories: thermal, gas and chemical methods. Generally, they involve the injection of fluids into the reservoir to generate favorable fluid properties or interfacial conditions, overcoming forces trapping the oil and boosting oil production substantially [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In the earliest studies, clusters of all size were observed, with approximately power-law distributions (Iglauer et al, 2012). It had been found that cluster size can range from a single pore to multiple-pore configurations (Karpyn et al, 2010;Kumar et al, 2010;Iglauer et al, 2013). The blob size was directly related to the viscous force, and the blob surface area and volume had an impact on the mass transfer characteristics of the system (Al-Raoush and Willson, 2005).…”
Section: Introductionmentioning
confidence: 99%